Nutritional quality and greenhouse gas emissions of vegetarian and non-vegetarian primary school meals: A case study in Dijon, France - Dahmani, Justine; Nicklaus, Sophie; Grenier, Jean-Michel; Marty, Lucile (Frontiers in Nutrition, 2022)
Since 2018 in France, national regulation mandates that school canteens serve a weekly vegetarian meal to reduce school canteens’ environmental impact in addition to previous regulations imposing nutritional composition guidelines. However, a lunch without meat is often perceived as inadequate to cover the nutritional needs of children. The present study aims to assess the nutritional quality and greenhouse gas emissions (GHGE) of vegetarian and non-vegetarian school meals served in primary schools in Dijon, France. The catering department provided the composition of 249 meals served in 2019 and nutritional content and GHGE were retrieved from national food databases. The portion size of each meal component was the standard portion size recommended by the relevant French authority (GEMRCN). Meals were classified into vegetarian meals, i.e., without meat or fish (n = 66), or non-vegetarian meals (n = 183). The nutritional adequacy of the meals for children aged from 6 to 11 years was estimated using the mean adequacy ratio (MAR/2000 kcal) as the mean percentage of daily recommended intake for 23 nutrients and the mean excess ratio (MER/2000 kcal) as the mean percentage of excess compared to the maximum recommended value for three nutrients, considering lunch as the only source of energy for a daily intake of 2000 kcal. This analysis of actual school meals shows that both vegetarian and non-vegetarian meals had a similar good nutritional quality with a MAR/2000 kcal of 87.5% (SD 5.8) for vegetarian and of 88.5% (SD 4.5) for non-vegetarian meals, and a MER/2000 kcal of 19.3% (SD 15.0) for vegetarian and of 19.1% (SD 18.6) for non-vegetarian meals. GHGE were more than twofold reduced in vegetarian compared to non-vegetarian meals (0.9 (SD 0.3) vs. 2.1 (SD 1.0) kgC02 eq/meal). Thus, increasing the frequency of vegetarian meals, by serving egg-based, dairy-based or vegan recipes more frequently, would reduce the GHGE of meals while maintaining adequate nutritional quality of primary school meals.